Politically driven cycles in fiscal policy: Evidence from disaggregated budgets in middle-income countries - Sri Fatmawati; Ardyanto Fitrady; Tri Widodo (Economies, 2025)
This paper examines the electoral cycle and the conduct of the central government's fiscal policy. It uses a panel database with disaggregated spending and revenue series for 34 middle-income countries over 2000-2022. A dynamic panel approach was used to look at overall government spending and income, and their parts, to find budget patterns during election seasons. The analytical methodology employs the two-step system generalized method of moments to address endogeneity concerns. The dynamic effect captured by the first lag of budgetary indicators suggests that the widening of that indicator is persistent. There is evidence that the current government is opportunistic, which suggests that the electoral cycle affects fiscal performance, especially when it comes to spending on economic matters and taxes on income, profits, and capital gains. Policymakers should be more aware of the government's opportunistic impact during the electoral period. To keep the budget stable, regulating corruption and having a democratic attitude might lessen the effects of the electoral cycle.
Keywords: 330; political budget cycle; fiscal indicator; control of corruption; democracy level; middle-income countries; two-step GMM